2022
DOI: 10.1111/eip.13268
|View full text |Cite
|
Sign up to set email alerts
|

Impact on public attitudes of a mental health audio tour of the National Gallery in London

Abstract: Aim: The arts have the potential to increase public awareness about mental health and reduce stigma. However, arts-based projects to raise awareness have been smallscale. In this study, a mental health-awareness audio tour of The National Gallery in London was co-produced and narrated by young adults with relevant lived experience. The study investigated the acceptability of the tour to the public and evaluated its impact on public attitudes about mental health.Methods: Participants were Gallery visitors over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Gallery visitors were led on ten stops through the gallery, focusing on artworks, challenging common myths about mental health, and inviting visitors to consider their personal views. The tour increased positive attitudes, indicating the feasibility of arts-based interventions in reducing stigma ( 32 ).…”
Section: The Association Between Psyche and Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallery visitors were led on ten stops through the gallery, focusing on artworks, challenging common myths about mental health, and inviting visitors to consider their personal views. The tour increased positive attitudes, indicating the feasibility of arts-based interventions in reducing stigma ( 32 ).…”
Section: The Association Between Psyche and Artmentioning
confidence: 99%
“…Turning from a national event to an international one in its second year, and doubling the number of artworks, reflects its potential to become a worldwide movement against mental health issues. This festival planned to provide an anti-stigma model coordinated with active public participation, despite some prior art festivals where participants were only visitors of the artworks ( 30 , 32 ).…”
Section: “Art and Psyche Festival”mentioning
confidence: 99%
“…The literature has established myriad positive health and well-being impacts from participating in arts and cultural activities (Daykin, 2020). Researchers have also shown that museum and gallery programs can improve health and well-being (Morse, 2015;Riches et al, 2022;. By way of example, in a project that responded to a need established by surveying 32 specialist museums in the UK, Thomson and Chatterjee (2015) developed a "set of 'pick and mix' measures designed to assess levels of well-being arising from participation in museum activities and events" (p. 49).…”
Section: Impact Framework In the Community Social And Health Fieldsmentioning
confidence: 99%